Pengaruh Waktu Pengadukan Terhadap Stabilitas Dan Karakteristik Fisik Food Grade Grease Halal Dari CPO Tangki Timbun PT. ABC - Riska Agustin; Nina Hairiyah; Fatimah; Imron Musthofa (JURNAL AGROINDUSTRI HALAL, 2025)
The utilization of Crude Palm Oil (CPO) as a raw material for halal food grade grease represents a strategic effort to diversify palm oil downstream products, enhance added value, and reduce dependence on imported food lubricants. This study aims to evaluate the effect of stirring time variations (15, 30, and 45 minutes) on the stability and physical characteristics of halal food grade grease formulated from storage tank CPO of PT. ABC The process involved bleaching of CPO, blending with additives (NaOH, stearic acid, and acetic acid), followed by testing of pH, melting point, organoleptic properties, emulsion stability, and color stability. ANOVA analysis revealed that stirring time significantly affected color, aroma, and texture (p < 0.05). Longer stirring duration decreased pH from 9.33 to 9.06, while increasing the melting point from 148 °C to 158 °C. All formulations maintained color and emulsion stability during six weeks of storage. These findings indicate that optimization of stirring time plays a crucial role in producing halal food grade grease from CPO with desirable stability and physical properties, supporting the development of a sustainable halal agroindustry.